Ringtones of opportunity : policy, technology and access in Caribbean communications - Dunn, Hopeton S. (Ian Randle Publishers KingstonJM, 2012)
Seeks to present research-based data and critical analyses on developments in the information and communication (ICT) sector within the Caribbean region, and to posit options for the way foward.